TORTONIAN CLYPEASTER FAUNA (ECHINOIDEA: CLYPEASTEROIDA) FROM GAVDOS ISLAND (GREECE - Tsaparas, N.; Antonarakou, A.; Marcopoulou-Diakantoni, A.; Dermitzakis, M. D.; Drinia, H. (Bulletin of the Geological Society of Greece, 2007)
The Tortonian sediments of Gavdos Island (Greece) contain a rich and diverse echinoidfauna. Clypeasteroid (sand dollars) echinoids are an important component of this fauna and sixteen taxa are recognized. Of these, eleven species are new records for Gavdos Island. The present paper is an annotated species list along with notes on certain aspects of the ecology of the determined echinoderms.